2015
DOI: 10.1111/bph.12885
|View full text |Cite
|
Sign up to set email alerts
|

DNA demethylation and invasive cancer: implications for therapeutics

Abstract: One of the hallmarks of cancer is aberrant DNA methylation, which is associated with abnormal gene expression. Both hypermethylation and silencing of tumour suppressor genes as well as hypomethylation and activation of prometastatic genes are characteristic of cancer cells. As DNA methylation is reversible, DNA methylation inhibitors were tested as anticancer drugs with the idea that such agents would demethylate and reactivate tumour suppressor genes. Two cytosine analogues, 5-azacytidine (Vidaza) and 5-aza-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 152 publications
2
57
0
Order By: Relevance
“…Newer studies indicate that CpG methylation within gene bodies can be associated with gene activation [34,35]. DNA methylation is regulated by the activities of DNA methyltransferases (DNMT1, DMNT3a and DMNT3b) and multiple DNA demethylases [36,37]. Numerous investigations have shown that CpG islands of DNA are globally hypomethylated in a number of cancer cell types, and that the aberrant expression of specific genes in cancer cells is in part due to demethylation of normally DNA methylated genes [34,[38][39].…”
Section: Evidence For Epigenetic Regulation In Stromal Cellsmentioning
confidence: 99%
“…Newer studies indicate that CpG methylation within gene bodies can be associated with gene activation [34,35]. DNA methylation is regulated by the activities of DNA methyltransferases (DNMT1, DMNT3a and DMNT3b) and multiple DNA demethylases [36,37]. Numerous investigations have shown that CpG islands of DNA are globally hypomethylated in a number of cancer cell types, and that the aberrant expression of specific genes in cancer cells is in part due to demethylation of normally DNA methylated genes [34,[38][39].…”
Section: Evidence For Epigenetic Regulation In Stromal Cellsmentioning
confidence: 99%
“…Aberrations in DNA methylation patterns, including increase (hypermethylation) in certain regions and decrease (hypomethylation) in others, have been linked to cancer initiation, progression, and metastasis [8,13]. Hypermethylation of tumor suppressor genes linked to transcriptional silencing, and recently reported promoter hypomethylation linked to activation of oncogenes and pro-metastatic genes have been described in tumor tissues from nearly all types of cancer including HCC [8,[14][15][16]. Ethanol intake, for instance, decreases levels of a ubiquitous methyl donor S-adenosylmethionine (SAM) in hepatic cells, which subsequently results in global DNA hypomethylation of the liver tissue, and leads to liver cirrhosis and HCC [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer metastasis is the spread of tumor cells from the original neoplasm to other organs through angiogenesis, invasion, colonization, and proliferation [30]. 5‐azaC treatment was reported to upregulate the prometastatic genes urokinase plasminogen activator, matrix metalloproteinase 2, metastasis‐associated gene 1, and CXC chemokine receptor 4, which stimulate cancer cell invasiveness and metastasis, in the non‐invasive breast cancer cell line MCF‐7 [31].…”
Section: Resultsmentioning
confidence: 99%